SEMIOTIC ELEMENTS OF BARTHESIAN MODEL ON “ZOOEY DESCHANEL” PANTENE SHAMPOO PRINT ADVERTISING - Juniato Sidauruk (Wanastra: Jurnal Bahasa dan Sastra, 2019)
Abstract  -- Print advertising contains several elements that can be discussed linguistically. There are semiotic elements commonly found in advertisements. There are lack discussion from researchers deal with semiotic elements in advertisements. There are three advertisements that will be analyzed in this research. The objective of this research is to find out semiotic elements in the Pantene Shampoo print advertising of “Zooey Deschanel” edition. The analysis is focused on semiotic elements by referring to Roland Barthes -- is commonly known as Barthesian Model. Barthes classified semiotic elements into Denotative, Connotative, and Myth. The analysis is presented by using descriptive qualitative method. Barthes’ Order of Signification will be the main pattern used to do the analysis. The results indicate that there are some signs found in the advertisements that contain semiotic elements. Eagerly saying that those three advertisements contain all semiotic elements as mentioned on order of signification from Roland Barthes. The writers found 32 signs in all advertisements, Signifier; and Connotative Signifier dominates all signs. The semiotic elements discussion can be used as raw model for next researchs. Beside that,  this discussion will inform and helpful to the advertisement producers, and alert them to think of all and consider the semiotic elements in their ads. The creators of the advertisements have to make it easy to understand by the public or target market of the product. Keywords: Print Advertising, Semiotics Elements, Sign, Signifier, Connotative Signifier.